التنصير: أهدافه، وسائله، سبل المقاومة - خياط، ندى بنت حمزة بن عبده (عبد الفتاح محمود ادريس, 2015)
Undoubtedly, leak weakness and weakness in the belief of some Muslims, encouraging other faiths to attract them to shift their religion to other religions, and the advocates of Christianity among the advocates of this shift, to attract the faint of faith of its adherents to Islam to convert to Christianity, putting in to make it happen ways several, perhaps the most important: the fight against the principles of Islam and its values faces and different ways, and so it was this research, which shows some of the objectives of Christianization, preachers and methods, and ways of their resistance, and thwart their plans, and to prevent them from achieving their goals.
مما لا مرية فيه, تسرب الوهن والضعف في معتقد بعض المسلمين, مما شجع أصحاب الديانات الأخرى على اجتذابهم للتحول عن دينهم إلى الديانات الأخرى, وكان المنصرون من بين الداعين إلى هذا التحول, لاجتذاب ليني العقيدة من المنتسبين إلى الإسلام لاعتناق النصرانية, متخذين لتحقيق ذلك سبلا عدة, لعل من أهمها: محاربة مبادئ الإسلام وقيمه بوجوه وطرق مختلفة, ولذا كان هذا البحث, الذي يجلي بعض أهداف التنصير, وأساليب دعاته, وسبل مقاومتهم, وإفشال مخططاتهم, والحيلولة بينهم وبين تحقيق مآربهم.
Keywords: التنصير; الإرساليات التبشيرية; الإسلام والمسيحية